1998
DOI: 10.1097/00006123-199812000-00096
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Expression after Traumatic Brain Injury and Neuroprotection with Aminoguanidine Treatment in Rats

Abstract: These data indicate that iNOS is expressed after moderate parasagittal fluid-percussion brain injury, in a time-dependent manner, and that inhibition of iNOS synthesis improves histopathological outcomes. Thus, inhibition of iNOS activation may represent a potential therapeutic strategy for the treatment of TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
72
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 62 publications
11
72
1
Order By: Relevance
“…The role of nitric oxide (NO) in the pathophysiology of cerebral ischemia (Ashwal et al, 1998;Dalkara and Moskowitz, 1994;Iadecola, 1997;Stagliano et al, 1997) and trauma (Wada et al, 1998a;Wada et al, 1998b) has also been documented. In ischemic models, abnormal NO production may be both beneficial and detrimental, depending upon when and where this diffusible neurotransmitter is released (Iadecola, 1997).…”
Section: Biochemical Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of nitric oxide (NO) in the pathophysiology of cerebral ischemia (Ashwal et al, 1998;Dalkara and Moskowitz, 1994;Iadecola, 1997;Stagliano et al, 1997) and trauma (Wada et al, 1998a;Wada et al, 1998b) has also been documented. In ischemic models, abnormal NO production may be both beneficial and detrimental, depending upon when and where this diffusible neurotransmitter is released (Iadecola, 1997).…”
Section: Biochemical Responsesmentioning
confidence: 99%
“…In contrast, NO produced by endothelial NOS (eNOS) can be of benefit by improving vascular dilation and perfusion (Huang et al, 1996). Generally, NO produced by the inducible form of NOS (iNOS) has been reported in models of cerebral ischemia (del Zoppo et al, 2000) and trauma (Wada et al, 1998b) to have detrimental effects on outcome. Increased iNOS activity generally occurs in a delayed fashion after brain ischemia and trauma and is associated with inflammatory processes.…”
Section: Biochemical Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxynitrite is formed by the chemical reaction of nitric oxide (•NO), produced by nitric oxide synthase (NOS), with superoxide radical (O 2 • −) whenever the two are produced in close proximity (Saran et al, 1990). All three NOS isoforms (eNOS, iNOS, and nNOS), as a key element in production of PN, have been shown to be up-regulated in brain tissue following TBI (Cobbs et al, 1997); (Wada et al, 1998) (Gahm et al, 2000); (Orihara et al, 2001). In addition, a novel isoform of Ca ++ -sensitive NOS (mtNOS), discovered within mitochondria (Bates et al, 1995); (Lopez-Figueroa et al, 2000); (Giulivi, 2003), has been shown to contribute to mitochondrial production of •NO and PN (Radi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Based on the findings obtained with pharmacological inhibition of NOS or comparisons between NOS-deficient and wildtype mice, both protective 3,6 and harmful [3][4][5] effects of NO in experimental CNS injury have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%